Comparative Immunogenicity Evaluation of Characterized Chitosan-Based and Other Adjuvants for Inactivated Influenza Vaccines - L. M. Khantimirova; O. S. Kashirina; M. I. Chernikova; Y. M. Vasiliev (Эпидемиология и вакцинопрофилактика)
Chitosan-based adjuvants combine effectiveness, safety and economic feasibility and thus are quite promising for enhancement of influenza control via vaccination, however, problems of characterization and reproducibility remain unresolved; data on relations between physical-chemical characteristics (PCC) of the polymer and immunogenicity of chitosan-based adjuvants, as well as comparative evaluation with other adjuvants are needed. Groups of mice were immunized intramuscularly with inactivated influenza vaccines based on A/California/07/2009 (H1N1) strain with characterized adjuvants based on chitosan with varying PCC (molecular mass 700 and 10 kDa, deacetylation degree 85%; HMC and LMC, respectively) and its derivative (succinylated chitosan (SC)). Experimental formulations were also studied: an «oil-in-water» emulsion (ME) and a multi-component adjuvant (MS). Different adjuvants increased immunogenicity of the inactivated influenza vaccines by hemagglutinin inhibiting sera antibodies in varying patterns. HMC was more immunogenic than LMC, whereas SC even reduced immunogenicity of the vaccine. HMC was comparable to MS by immunogenicity, and LMC - to ME. PCC of chitosan and its derivatives play an important role in immunogenicity of the respective adjuvants, and perspective and characterized chitosan-based adjuvants are comparable or even more immunogenic than adjuvants from other groups.